Ocular Manifestations in Patients with Facial Seborrheic Dermatitis : Ocular Manifestations in Facial Seborrheic Dermatitis - Kumar, Peryanka Jagdesh; Kumar, Vijay; Khan, Beenish; Shams, Asma; Das, Narain; Devi, Vinesha (Pakistan Journal of Health Sciences, 2026)
Seborrheic dermatitis (SD) is a chronic inflammatory disorder, especially including the peri-orbital region, which leads to different types of ocular surface abnormalities. Objective: To assess the prevalence and pattern of ocular manifestations in patients having facial SD and to evaluate its correlation with the severity of disease. Methods: An analytical case-control study was conducted from January 2024 to June 2025 in the Department of Dermatology and Ophthalmology at Al-Tibri Medical College and Hospital. Ninety-one patients with clinically diagnosed facial SD and ninety-one age and sex-matched healthy controls were enrolled in the study. All participants underwent a detailed ophthalmic examination, including TBUT, Schirmer’s test, and slit-lamp evaluation. Data were analyzed by using SPSS version 26.0, and a p-value < 0.05 was taken as statistically significant. Results: Ocular symptoms were reported in 68.1% SD patients compared to 30.8% in controls (p < 0.001). Lid margin telangiectasia (50.5%), conjunctival hyperemia (48.4%), and meibomian gland dysfunction (57.1%) were significantly more common in SD patients (all p<0.001). Mean TBUT (6.2 ± 2.1 s) and Schirmer’s scores (9.5 ± 4.3 mm) were lower in SD patients than in controls (13.1 ± 3.9 s and 14.8 ± 4.5 mm; p < 0.001). Disease severity showed a strong negative correlation with TBUT and Schirmer’s test and a positive correlation with ocular surface staining (p < 0.001). Conclusion: Facial seborrheic dermatitis is frequently associated with significant ocular involvement. Early ophthalmologic evaluation is recommended.